THE INITIAL OUTCOME OF TREATMENT OF EXTENSIVE SKIN LOSS EXTREMITIES AFTER TRAUMA WITH A FREE PARASCAPULAR FLAP (Vietnam Journal of Community Medicine, 2026)
Objective:Evaluating the initial outcomeof treatment of extensiveskinlossextremitiesaftertraumawithafreeparascapularflap.Subjects and methods: This is a case series, prospective study. There were 5 patients during the period from March, 2025 to January, 2026 at the Faculty of Microsurgery and Reconstructive Surgery, Hospital for Traumatology and Orthopaedics at Ho Chi Minh city.Results: All flaps are alive and the donor site were directly closed. The average follow-up period was 6 months. The flap is of moderate thickness, which can be used to cover many areas of the hands and feet: 1 case on the back of the hand, 1 case on the sole of the foot, 3 cases on the back of the foot. The average size of the flap is 197 cm2, of which the largest flap is 21 × 11 cm.Conclusion: The use of a free parascapular flap to cover the soft tissue of the extremities is reliable. The flap has a constant blood supply, which can be raised with a large size and has moderate thickness. The position for the donor site can be closed primarily, the scar is aesthetic and does not limit movement.
Keywords: Scapular flap, parascapular flap, circumflex scapular artery perforator flap, free flaps.